Challenging Imperialism: Soldier’s Letters and the Anti-Imperialist League - Bailon, Rowena Q. (Philippine Social Sciences Review, 2021)
When Commanding General Elwell Otis imposed a strict censorship on news sent to the mainland United States of America in 1899, the soldiers’ letters became important sources of information on the events in the Philippines. While the letters were intended for the perusal of the soldiers’ family members, some of these came into the hands of the Anti-Imperialist League (AIL). Consequently, the Anti-Imperialists used these letters as tool in challenging the imperialistic pursuit of the United States government. This paper examines the role of soldiers’ letters in the antiimperialists fight for Philippine independence. Most of the letters utilized were gathered from different libraries in the US. Some of the letters were written by regular soldiers while others were written by volunteer soldiers. To countercheck some of the letters published by the AIL, letters that were not published, but presented the same views, were also taken into account. While the focus was on the soldiers’ letters in relation to their role as agents of empire, it will also look into the lives of the ordinary soldiers as letter writers connecting not only with their family and friends, but also with their communities back home.
Keywords: Philippine-American War, soldier’s letters, Anti-Imperialist League